Interpreting practice proficiency: Indonesia to English in socio-economic revitalization in Sungailiat tourism sector based on a survey study - Afandi, Rizky Arif; Ferianda, Sandy; Febiola, Tsasa Vina; Susanti, Tia Ayu (Universitas Mulawarman, 2025)
Proficiency in the practice of interpreting refers to one’s ability to effectively translate a source language into a target language while ensuring the meaning is conveyed accurately. This research specifically focused on the use of Indonesian as the source language and English as the target language, which is crucial in the tourism industry, especially in Sungailiat City. This research used a survey-based approach and uses supporting theory as a research methodology to investigate the effectiveness of translation practices from Indonesian to English. Data collection includes interviews and observations. The primary data obtained was analyzed to reveal the challenges faced by tour guides or shoreline security officers in implementing these practices, as well as the potential opportunities available to them through continued implementation. The results of this research can increase the awareness of professionals directly involved in the tourism industry and provide educational insights for tour guides and local communities managing tourist attractions. Additionally, it can contribute to improving the skills of guides, thereby expanding their knowledge to encourage socio-economic growth in the Sungailiat tourism sector.